The Stress And Emotional Eating Behavior In Students Of Universitas Negeri Semarang (Universitas Negeri Semarang, 2022)
Stress management is better known as a coping strategy for stress. One coping strategy of stress that is often done by students is through emotional eating behavior. Students who face academic stressors are at risk of increased food consumption. Based on research by nutrition students of FKM Universitas Airlangga, found that the heavier the stress experienced by students who compose the thesis, the higher the tendency of students to show excessive eating behavior or emotional eating. The purpose of this study was to find out the relationship between stress and emotional eating behavior in final-level students of Semarang State University. This type of research is using a quantitative research design with cross-sectional methods. The sample was set by 100 respondents with purposive sampling techniques. In this study, the bound variable that will be studied is emotional eating behavior, while the free variable is stress. The instruments used are questionnaires to collect data on stress and emotional eating behavior. Data is analyzed using chi-square tests using statistical data processing software programs that will later be obtained p-value. If the chi-square test requirements are not met, then the test used is an alternative test, namely the Kolmogorov Smirnov test because the variable is more than two categories or a 2xK table. The results of this study showed that there is a relationship between stress and emotional eating behavior in final-level students of Semarang State University (p =0.036).